THE INTEGRATION OF COMMUNICATION TECHNOLOGIES AND INTERACTIVE METHODS IN TEACHING THE SUBJECT OF " METHODS OF TEACHING INFORMATICS" - Madrakhimov Shukhratjon Shukurovich,Madrakhimova Makhfuza Akhmedovna,Muydinjonov Ziyodjon Rafiqjon Ugli; Muydinjonov Davlatjon Rafiqjon Ugli (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the use of the "Cognitive Map" method and the software "Mindmaster" in teaching "Analysis of the lesson in pedagogical activity" in the subject "Methods of teaching informatics".